Upaya Menjaga Kesehatan Mental Ibu dengan Anak Berkebutuhan Khusus melalui Program Pendampingan Psikologis dan Dukungan Sosial di Yayasan Sahabat Autis Bogor - Muh. Syafiq Marzuqi; Oktavia Oktavia; Gunarti Gunarti; Ria Savitri (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The implementation of this research, conducted through Community Service Activities, is grounded in the conditions experienced by parents in caring for children with special needs, such as autism spectrum disorder, ADHD, cerebral palsy, or other developmental disorders. The heavy burden of caregiving can increase the risk of psychological distress. This Community Service Activity was carried out at the Sahabat Autis Bogor Foundation, located in Billabong Permai Housing Complex, Block C3D No. 2, Bojong Gede, accompanying seven parents of students. The objective of the Community Service Activity was to enhance the quality of life of the mothers, stabilize their mental health, prevent mental health decline, and provide optimal support for their children with mental health challenges. The methods employed in the Community Service Activity included (1) Socialization and Seminar Implementation, (2) Psychological Support and Counseling, and (3) Coping Strategy Training and the Establishment of a Support Group. The findings from this research activity indicated that parents struggled to express the anger and bitterness they experienced as side effects of stress, fatigue, and the lack of attention to their own needs. Parents, particularly mothers of children with special needs, were found to be more vulnerable to prolonged stress, anxiety, and even depression compared to mothers of children without special needs. They also experienced trauma in introducing their children to their social environment and exhibited heightened concerns regarding their children's careers and futures.